If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.4p-2=0.8p-3
We simplify the equation to the form, which is simple to understand
0.4p-2=0.8p-3
We move all terms containing p to the left and all other terms to the right.
+ 0.4p-0.8p=-3+2
We simplify left and right side of the equation.
-0.4p=-1
We divide both sides of the equation by -0.4 to get p.
p=2.5
| 8x+2(x-9)=82 | | -7x=-4 | | 93x=27 | | 0=5.1x+0.3x | | 8x+12(x-9)=82 | | 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 |